Flavonoids as G Protein-coupled Receptors Ligands: New Potential Therapeutic Natural Drugs - Chda, Alae; Bencheikh, Rachid (Current Drug Targets, 2023)
G protein coupled receptors (GPCRs) are among the largest family of cell surface receptors found in the human genome. They govern a wide range of physiological responses in both health and diseases, making them one of the potential targeted surface receptors for pharmaceuticals. Flavonoids can modulate GPCRs activity by acting as allosteric ligands. They can either enhance or reduce the GPCR's effect. Emerging research shows that individual flavonoids or mixtures of flavonoids from plant extracts can have relevant pharmacological effects against a number of diseases, particularly by influencing GPCRs. In the present review, we are considering to give a comprehensive overview of flavonoids and related compounds that exhibit GPCRs activity and to further explore which beneficial structural features. Molecular docking was used to strengthen experimental evidence and describe flavonoid-GPCRs interactions at molecular level.
Keywords: flavonoids aglycones